MULTIMODAL PROTEST SYMBOLS AND IMPLICATIONS FOR CRITICAL LITERACY IN EFL EDUCATION - Aldiansyah, Fauzan (Direktorat Riset dan Pengabdian kepada Masyarakat, Universitas Bina Darma, 2025)
This study examines how multimodal protest symbols specifically the One Piece Straw Hat Pirates’ Jolly Roger flag and the Indonesian protest colors Brave Pink and Hero Green construct ideological and emotional meanings across digital activism in Indonesia and Nepal. These symbols were selected due to their high visibility and viral circulation in recent youth-led protest movements across the region. Drawing on Multimodal Discourse Analysis (MDA) and Critical Discourse Analysis (CDA), the research analyzes thirty publicly available images, memes, and social media posts collected between August and October 2025. The findings show that the Jolly Roger flag functions as a transnational emblem of defiance and youth solidarity, while Brave Pink and Hero Green emerge as localized color narratives expressing maternal bravery and working-class sacrifice in Indonesia. In Nepal, the Jolly Roger is used more uniformly as a universal symbol of unity, reflecting differences in symbolic variation rather than analytical emphasis. The study highlights how multimodal elements color, image, and text, cooperate to shape public sentiment and civic identity. Pedagogically, these findings demonstrate how authentic multimodal protest texts can be integrated into English as a Foreign Language (EFL) classrooms to develop learners’ critical literacy, visual interpretation skills, and intercultural awareness beyond linguistic forms.